2022
DOI: 10.1039/d1nr06545a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the local electronic structure of a single-site Ni catalyst by co-doping a 3D graphene framework with B/N atoms toward enhanced CO2 electroreduction

Abstract: Various single metal sites supported on N-doped carbon materials have been demonstrated to be the effective catalysts for CO2 electroreduction. However, it remains a challenging task to gain comprehensive understanding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…3f ). 26 Furthermore, as revealed by the EXAFS wavelet transform (WT) analysis and the resulting WT contour plots, in contrast to the intensity maximum that arises from the Ni-Ni bond at 7.18 Å −1 for Ni foil and the Ni-O bond at 4.46 Å −1 for NiO, only one intensity maximum at 3.66 Å −1 is found for Ni SAs-NCW, which is very close to that of NiPc (3.95 Å −1 ), which further confirms the Ni-N 4 coordination.…”
mentioning
confidence: 99%
“…3f ). 26 Furthermore, as revealed by the EXAFS wavelet transform (WT) analysis and the resulting WT contour plots, in contrast to the intensity maximum that arises from the Ni-Ni bond at 7.18 Å −1 for Ni foil and the Ni-O bond at 4.46 Å −1 for NiO, only one intensity maximum at 3.66 Å −1 is found for Ni SAs-NCW, which is very close to that of NiPc (3.95 Å −1 ), which further confirms the Ni-N 4 coordination.…”
mentioning
confidence: 99%
“…Additionally, Xiong et al . reported that, with the coordination of B in the higher coordination shell, the performance of Ni SACs can be enhanced [71] . Particularly, the catalyst named Ni−B 2 N 4 delivered the highest Faradaic efficiency of CO with 98% at the overpotential of −0.8 V, because the B‐doping changed the electronic structure of Ni and reduced the energy barrier of generating COOH*.…”
Section: Microenvironment Regulation Of C‐sacsmentioning
confidence: 99%
“…In recent decades, single-site catalysts (SSCs) have emerged as a new type of catalyst because of their precisely controllable structure and high atomic utilization efficiency. [9][10][11][12][13][14][15][16] The SSCs with active metal center isolated by non-metal atoms mainly contain single-atom catalysts (SACs), 17,18 homogeneous molecular catalysts (HMCs), 19,20 as well as metal organic framework-supported (MOF-supported) 21,22 and covalent organic framework-supported (COF-supported) SSCs. 23,24 The unique coordination environment of SSCs paves a new way for regulating the intrinsic charge, spinning order, and charge transfer of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the controllable structure of SSCs is also beneficial for the structural design of catalyst, study of reaction mechanism, and evolution of reaction products during the ECR reaction. 14,25–27 Numerous theoretical and experimental studies have demonstrated the application potential of SSCs in ECR. 28–31…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation